Structural change ramifications of consumer credit expansion in a two sector growth model - Esra Nur Uægurlu (University of Massachusetts, Department of Economics, 2021)
This paper analyzes the structural change implications of consumer credit expansions in a dual-sector open economy growth model. Policy-induced increases in banks' willingness and ability to lend result in new consumer lending, boosting consumption demand and average wages in the nontradable sector. Under the assumptions of fixed relative wages and mark-up pricing, wage pressures translate into in ationary pressures. The central bank, acting under the sole target of controlling in ation, raises the interest rate to contain in ationary pressures. This intervention causes a real exchange rate appreciation, followed by a loss of international competitiveness in the tradable sector. This way, the model illustrates that consumer credit expansions can trigger premature deindustrialization, shifting sectoral structure in favor of the nontradable sector. The formal model is inspired by the Turkish economy that experienced a notable expansion of consumer credit between 2002-2013.
Keywords: E58; F43; L16; O11; O41; 330; Consumer credit; structural change; economic growth; inflation targeting; real exchange rate